Adoptive immunotherapy of cancer: Gene transfer of T cell specificity - Al-Khami, Amir A (Landes Bioscience, 2011)
Adoptive transfer of tumor-reactive T cells has emerged as a promising advance in tumor immunotherapy. Specifically, infusion of tumor-infiltrating lymphocytes has led to long-term objective clinical responses for patients with metastatic melanoma. Donor lymphocyte infusion is also an effective treatment of post-transplant lymphoproliferative disease. However, adoptive T cell therapy has restrictions in the isolation and expansion of antigen-specific lymphocytes for a large group of patients. One approach to circumvent this limitation and extend adoptive immunotherapy to other cancer types is the genetic modification of T cells with antigen-specific receptors. In this article, we review strategies to redirect T cell specificity, including T cell receptor gene transfer and antibody receptor gene transfer.